Eksistensi Laki-Laki Sebagai Pengrajin Tenun Songket Di Nagari Pandai Sikek: Eksistensi Laki-Laki Sebagai Pengrajin Tenun Songket Di Nagari Pandai Sikek - Lisa Afista; Indraddin; Maihasni (Jurnal Sosiologi Nusantara, 2024)
Being a songket weaving craftsman is not only done by women, but men can also do it. This research aims to determine the existence of men as songket Pandai Sikek weaving craftsmen. This research uses a qualitative approach with phenomenological methods. Data collected using observation, in-depth interviews, and documentation studies. The results of this study found that men began to become songket weaving craftsmen in Pandai Sikek village during the monetary crisis in Indonesia in 1998. The craftsmans wages are not too great. They made the loom work an additional work a side job. At this time, economic factors are the main driver of men deciding to become songket weaving craftsmen. Men become weaving craftsmen are people who have the skills to weave. Men also have the potential to become songket weaving craftsmen pandai sikek. Effort made to maintain this existence among other things, learning to weave from a young age, doing work according to what the boss orders, completing woven cloth on time, arraning strategies for working on woven cloth, developing innovative looms from traditional to ATBM (Alat Tenun Bukan Mesin), maintaining the quality of woven cloth, maintain good relationships with boss and co-workers.